La atención temprana y su influencia en el desarrollo motriz grueso en los niños de 2 a 5 años de edad con parálisis cerebral, que asisten al centro de rehabilitación para niñas, niños y jóvenes con discapacidad Sendero de Alegría, de la ciudad de Loja. Periodo 2014 - Maza Maza, Maricela Delfina (2016)
This research was headed for the purpose of applying care how early influences large motor development in children 2-5 years old with cerebral palsy, who attend the rehabilitation center for children and youth with disabilities Trail Joy city of Loja. To comply with the same methods were used: Scientific, Quantitative, Analytical, inductive-deductive, hermeneutical method, descriptive statistical method; tools: Adaptation of psychomotor development test TEPSI 0-5 years as a result of the investigation it was determined that the sample initially comprised of 5 children / as with Cerebral Palsy 2-5 years found that balance in paragraphs, muscle tone, locomotion most children lies in the assessment of late, and during the implementation of early intervention activities (balance, muscle tone, locomotion) witnessed a gradual improvement and revaluation in the balance parameter , muscle tone and locomotion, most are in the risk indicator. After obtaining the results we conclude that through the stimulation will provide the infant situations that invite them to learning. The idea is to open sensory channels for the child to acquire more information about the world around him. It will be important to know the child and evaluate it with a focused observation, to know where to begin to offer the experiences, emphasizing areas of development while stimulating go different functions as attention, memory, language. Therefore it is recommended to perform more activities for them to improve skills that boost gross motor development.